Super/subcritical fluid chromatography with packed columns: state of the art and applications - Carla Grazieli Azevedo da Silva (Química Nova, 2014)
Separations using supercritical fluid chromatography (SFC) with packed columns have been re-discovered and explored in recent years. SFC enables fast and efficient separations and, in some cases, gives better results than high performance liquid chromatography (HPLC). This paper provides an overview of recent advances in SFC separations using packed columns for both achiral and chiral separations. The most important types of stationary phases used in SFC are discussed as well as the most critical parameters involved in the separations and some recent applications.